The role of integrated marketing communication, ecological knowledge and co-creation of value toward visitor satisfaction in the hotel industry - Hadi, Antonius Satria (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2023)
This research aims to examine the effect of integrated marketing communication on visitor satisfaction mediated by ecological knowledge and co-creation of value. Respondents in this study were 150 tourists who have stayed at hotels in Yogyakarta. This research has five hypotheses. The analytical technique used in this research were confirmatory factor analysis (CFA) and structural equation model (SEM) using SmartPLS 3 software. The results of this research empirically prove that integrated marketing communication positively affects visitor satisfaction mediated by ecological knowledge and co-creation of value. Each of the hypotheses was accepted and discussed in detail in this article.